Four desert fathers: Pambo, Evagrius, Macarius of Egypt, and Macarius of Alexandria ; Coptic texts relating to the Lausiac history of Palladius - Vivian, Tim; Greer, Rowan A. (St. Vladimir's Seminary Press "popular patristics" series, 2004)
The life of Pambo -- The life of Evagrius -- The life of Macarius the Great -- The life of Macarius of Alexandria -- Seven goals of anti-origenism -- Syriac lausiac history -- Evagrius debates three demons (Cotelier) -- Apa Aphou and Archbishop Theophilus -- Debate the image of God.